HISTORY AND DEVELOPMENT OF ISLAM IN KINABUHUTAN VILLAGE - Malawat, Afriani; Mimpia, Supardi; Djiko, Rahmawati (Historia Islamica: Journal of Islamic History and Civilization, 2024)
This research examines the history and development of Islam in Kinabuhutan Village, which was originally part of Talise Village in North Minahasa, Indonesia. Islam entered the area around 1952, spearheaded by the migration of 10 Muslim families from Talise to Kinabuhutan, started by a foreman who married a local woman. Since then, the village has developed into a fully Muslim community, with the establishment of a mosque and active religious activities. Kinabuhutan village was officially split from Talise village on February 15, 2006, to overcome geographical challenges and improve public services. This research highlights the role of Muslim traders and scholars in the spread of Islam in Indonesia, particularly in coastal areas, as well as the unique context of the spread of Islam in an area dominated by Christian influence. The research methods used include qualitative and historical approaches, including sociological and anthropological approaches, to analyze the role of Islam in the community. The results show that Islam began to enter Kinabuhutan Village around 1952, spearheaded by the migration of 10 Muslim families from Talise. The village later developed into a fully Muslim community, with the establishment of a mosque and active religious activities. Kinabuhutan Village was officially divided from Talise Village on February 15, 2006, to overcome geographical challenges and improve public services.